Feelings. - Frosh, Stephen (Taylor & Francis, 2011)
Everyone talks about their feelings, but what exactly are they? What are the distinguishing features of feelings, and how do they differ from emotions and affects? How do our feelings influence the kinds of people we are, and the sorts of communities and societies in which we live? In this wonderful short book, acclaimed author Stephen Frosh interrogates the terrain of feelings and asks how this 'hidden' dimension of the self helps shape our worlds. The book provides an accessible and thought-provoking introduction to the major debates around feelings in the modern world. Feelings is an accessi.